2015
DOI: 10.1007/s11274-015-1947-6
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency transformation of stevioside into a single mono-glycosylated product using a cyclodextrin glucanotransferase from Paenibacillus sp. CGMCC 5316

Abstract: Stevioside is a non-caloric, natural, high-intensity sweetener. However, the bitter aftertaste of stevioside restricts its utilization for human consumption and limits its application in the food industry. In this study, a high efficiency enzymatic modification system was investigated to improve stevioside taste quality. A cyclodextrin glucanotransferase (CGTase) producing strain Paenibacillus sp. CGMCC 5316 was isolated from Stevia planting soil. With starch as glycosyl donor, this CGTase can transform stevio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Therefore, significant research effort has been focused on the addition of glycosyl moieties in steviol glycosides, aiming at the improvement of their organoleptic properties. Cyclodextrin glucanotransferases (CGTases, 1,4-α-d-glucan: 1,4-α-d-glucopyranosyltransferase, cyclizing, EC 2.4.1.19) are the most common enzymes used for steviol glycosides transglycosylation, introducing α-1,4 glycosidic bonds with very high yields, exceeding 70% ( Li et al, 2013 ; Yu et al, 2015 ; Zhang et al, 2015 ). However, the hydrolysis of α- 1,4 bonds by human amylases can increase the caloric value of the modified steviosides, resulting in a final product with low appeal to target consumer groups, e.g., diabetics ( Gerwig et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, significant research effort has been focused on the addition of glycosyl moieties in steviol glycosides, aiming at the improvement of their organoleptic properties. Cyclodextrin glucanotransferases (CGTases, 1,4-α-d-glucan: 1,4-α-d-glucopyranosyltransferase, cyclizing, EC 2.4.1.19) are the most common enzymes used for steviol glycosides transglycosylation, introducing α-1,4 glycosidic bonds with very high yields, exceeding 70% ( Li et al, 2013 ; Yu et al, 2015 ; Zhang et al, 2015 ). However, the hydrolysis of α- 1,4 bonds by human amylases can increase the caloric value of the modified steviosides, resulting in a final product with low appeal to target consumer groups, e.g., diabetics ( Gerwig et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the cyclization reaction (CD production), this enzyme also catalyzes other two intermolecular transglycosylation reactions (coupling and disproportionation) and the hydrolysis reaction of the starch [3,5]. Although it is mainly used at industrial scale for the production of cyclodextrins, recent studies performed by Yu et al [6] have demonstrated that CGTase from Paenibacillus sp. CGMCC 5316 can be used to eliminate the bitter taste of a natural sweetener known as stevioside by a reaction of transglycosylation using starch as a glucose donor.…”
Section: Introductionmentioning
confidence: 99%
“…For example, rebaudioside D (Figure 1s) and rebaudioside M, which carry two and three C-19 linked glycosyl units, respectively, both demonstrate improved edulcorant quality over that of stevioside or rebaudioside A. Hence, enzymatic glucosylation of stevioside and rebaudioside A have been extensively studied to improve the edulcorant quality; , the resultant products are so-called glucosyl steviol glycosides (GSGs).…”
Section: Introductionmentioning
confidence: 99%
“…In industry, the most popular glucosyltransferases, such as CGTase and other α-amylase, have been extensively applied to catalyze the transglucosylation of stevioside or rebaudioside A with dextrins as glucosyl donors. ,, ,,, The CGTase-intermediated reaction has multiple pathways that could yield many products via hydrolysis, coupling, and disproportionation . The obtained GSGs that possess a high percentage of glucosyl units are used as sweet flavoring agents in both perfumes and drug formulas .…”
Section: Introductionmentioning
confidence: 99%